Wood Production and Management of Woody Species in Homegardens Agroforestry: The Case of Smallholder Farmers in Gimbo District, South West Ethiopia - Yakob, Getahun; Asfaw, Zebene; Zewdie, Solomon (International Journal of Natural Sciences Research, 2014)
Homegardens are defined as a system of production of diverse plant species, which can be adjacent to household or slightly further away and is easily accessible. Wood production and management systems of Kaffa homegardens are poorly known. The study was conducted to assess the wood production and farmers’ strategy of managing woody species in Gimbo district, South West Ethiopia. A complete homegarden woody species inventory was carried out to collect vegetation data, while simple random sampling was used to select sample households within wealth categories. From two purposely selected sites, a total of 120 households were selected for interview and vegetation data collection. Semi-structured interviews, direct observation and focus group discussions were employed to gather information on farmers’ strategy of managing woody species. The DBH of all trees and shrubs ≥ 5cm was measured. The mean number of stems per garden was 34, ranging between 6 to 99. Wealth status of the household influenced the wood production of homegardens. At all studied villages, the largest number of stems per garden was recorded on gardens of wealthy households. Various trees and shrubs are managed on the same piece of land. About 92% of the respondents have retained different woody species in their homegardens while converting the original forest to settlement areas. Some woody species like Millettia ferruginea, Vernonia amygdalina, Ficus sur, Croton macrostachyus and Sapium ellipticum were more frequently retained than others. In general, the reasons for planting woody species were income generation, shade and fruit, in increasing importance order. About 96 % of the respondents did practice different types of management activities for the woody species they owned. The common management practices carried out in the homegardens were thinning, pruning, fertilizing, watering, protection, coppicing and lopping. However, only 2% of the respondents did practice compost preparation. Diseases of coffee and fruit trees were the major problem faced by the farmers in woody species management. Therefore, it is recommended that appropriate intervention either through research or extension has to take place in order to reduce the impacts.